A novel Bxb1 integrase RMCE system for high fidelity site‐specific integration of mAb expression cassette in CHO Cells. Issue 8 (14th March 2017) - Inniss, Mara C.; Bandara, Kalpanie; Jusiak, Barbara; Lu, Timothy K.; Weiss, Ron; Wroblewska, Liliana; Zhang, Lin
ABSTRACT: As CHO cell line development for biotherapeutic production becomes more sophisticated through the availability of the CHO genome sequence, the ability to accurately and reproducibly engineer the host cell genome has become increasingly important. Multiple well characterized systems for site‐specific integration will enable more complex cell line engineering to generate cell lines with desirable attributes. We built and characterized a novel recombinase mediated cassette exchange (RMCE) system using Bxb1 integrase and compared it to the commonly used Flp/FRT RMCE system. We first integrated a DNA construct flanked by either Bxb1 attachment sites or FRT sequences (referred to as a landing pad) into the Fer1L4 genomic locus of CHO‐S cells using CRISPR/Cas9 mediated homologous recombination. We characterized the resulting clones harboring either the Bxb1 or Flp/FRT landing pad using whole genome resequencing to compare their genomes with the parental host cell line. We determined that each landing pad was specifically integrated into the Fer1L4 locus in the selected clones and observed no major structural changes in the genome or variations in copy number as a result of CRISPR/Cas9 modification. We subsequently tested the ability of the Bxb1 and Flp/FRT landing pad clones to perform proper RMCE with donor vectors containing identical mAb expression cassettes flanked by either Bxb1 attachment sites or FRT sites. We demonstrated that both RMCE systems were able to generate stable pools in a similar time frame with comparable mAb expression. Through genetic characterization of up to 24 clones derived from either system, we determined that the BxB1 RMCE system yielded higher fidelity RMCE events than the Flp/FRT system as evidenced by a higher percentage of clones with expected integration of the mAb cassette into the landing pad in the respective cell lines. We conclude that Bxb1 RMCE is an excellent alternative to Flp/FRT RMCE and valuable addition to our toolbox enabling the engineering of more sophisticated cell lines for biotherapeutic production. Biotechnol. Bioeng. 2017;114: 1837–1846. © 2017 Wiley Periodicals, Inc. Abstract : CRISPR/Cas9 mediated homologous recombination was used to integrate either Bxb1‐RMCE landing pad or Flp‐RMCE landing pad at a pre‐defined locus in the CHO‐S host genome. The ability of a Bxb1‐RMCE system to generate recombinant cell lines expressing monoclonal antibody was compared to the Flp‐RMCE system. We show that the Bxb1‐RMCE system enables highly accurate integration of mAb expression cassette and is an excellent alternative to Flp‐RMCE.